Spiritual and mental harmonization: religious education through the lens of psychology - Tobroni, Tobroni; Faridi , Faridi; Rizqiani, Ika Sofia (Al-Misbah (Jurnal Islamic Studies), 2025)
This research offers a new, holistic, and multidisciplinary perspective on Islamic Religious Education by combining spiritual and psychological paradigms. The study adopts a literature review method, which involves several stages: identifying sources, selecting and filtering relevant literature, collecting information, and analyzing and synthesizing data. The findings show that effective Islamic Religious Education should integrate the spiritual, emotional, and cognitive aspects of learners. By considering students’ psychology, interests, motivations, and talents, religious education can serve as a powerful tool for building mental and spiritual well-being. Educators, as spiritual guides, play a vital role in creating meaningful connections between religious teachings and students’ daily lives. Students with spiritual awareness and a positive attitude are believed to experience beneficial effects on other aspects of their personal lives. The implications of these findings suggest that when students’ psychological development, interests, motivations, and talents are balanced with spirituality, spiritual and mental harmony can become a source of happiness, serenity, and life’s meaning.